2020
DOI: 10.1073/pnas.2006596117
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of electrohydraulic soft actuators

Abstract: Nature has inspired the design of robots in which soft actuators enable tasks such as handling of fragile objects and adapting to unstructured environments. Those tasks are difficult for traditional robots, which predominantly consist of hard components. Electrohydraulic soft actuators are liquid-filled shells that deform upon the application of electric fields; they excel among soft actuators with muscle-like force outputs and actuation strains, and with actuation frequencies above 100 Hz. However, the fundam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 40 publications
(70 reference statements)
0
50
0
Order By: Relevance
“…Optimization of the pump design would improve the performance, although the measured flow rate (13.8 μL min −1 at 1 Hz) is already comparable with other elastomeric pumps driven by DEAs [ 26,27 ] and is currently limited by the slow unzipping of the actuators, which limits the actuation frequency. The dynamics of zipping actuators with liquid dielectric is complex [ 66 ] and depends on many parameters, including the viscosity of the liquid, the geometry of the actuator, the impedance of the fluidic circuit, and the pressure in the two fluidic circuits.…”
Section: Resultsmentioning
confidence: 99%
“…Optimization of the pump design would improve the performance, although the measured flow rate (13.8 μL min −1 at 1 Hz) is already comparable with other elastomeric pumps driven by DEAs [ 26,27 ] and is currently limited by the slow unzipping of the actuators, which limits the actuation frequency. The dynamics of zipping actuators with liquid dielectric is complex [ 66 ] and depends on many parameters, including the viscosity of the liquid, the geometry of the actuator, the impedance of the fluidic circuit, and the pressure in the two fluidic circuits.…”
Section: Resultsmentioning
confidence: 99%
“…A major advantage of Peano-HASEL actuators is their use of a fast electrohydraulic mechanism (Kellaris et al, 2018 ). The dynamics of Peano-HASEL actuators under different loads and operating conditions were studied in detail by Rothemund et al ( 2020 ). To highlight the fundamental benefits and drawbacks of the Peano-HASEL and DC motor actuators, the dynamics of the prosthetic finger system in this work were studied under no load.…”
Section: Resultsmentioning
confidence: 99%
“…With the custom finger, maximum speed of flexion was 10.6 times greater and the bandwidth was 11.1 times greater than the DC motor actuator. Reduced pouch dimensions and lower viscosity dielectric fluids could lead to even faster actuation (Rothemund et al, 2020 ). This dynamic performance will become even more important as improved myoelectric control algorithms become available for prosthetic hands.…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Extensive research demonstrated that the self-assembly of small-scale structures can be achieved along liquid interfaces, opening ways to inexpensive manufacture processes in between bottom-up and topdown forms of fabrication. [3][4][5][6][7][8][9] Capillary driven self-assembly consists in suspending small objects at the water-air interface. Depending on the object weight, hydrophobicity and surface tension, the interface is slightly deformed, inducing a net force between the particles.…”
Section: Introductionmentioning
confidence: 99%